Accuracy evaluation of tridimensional images performed by portable stereophotogrammetric system - Alvaro Augusto JUNQUEIRA-JÚNIOR; Laís Valencise MAGRI; Mateus Sgobi CAZAL; Aline Akemi MORI; Ana Maria Bettoni RODRIGUES DA SILVA; Marco Antônio Moreira RODRIGUES DA SILVA (Universidade Estadual Paulista, 2019)
Abstract Introduction Human facial characteristics vary according to individual dental occlusion, facial harmony, orofacial musculature and the format and configuration of craniofacial structures. Traditionally, anthropometric measurements have been acquired through direct evaluation of subjects in a clinical environment using calipers and metric tapes to measure distances between arches and landmarks. Scientific breakthroughs have enabled the digitization of data and introduced the possibility of quick, precise, radiation-free acquisitions; details can be archived for future analysis and easily shared with patients and colleagues. Among new facial analysis methods, the stereophotogrammetry technique has emerged, which uses a group of cameras to take many photographs of a subject in rapid succession from multiple angles. Nowadays, portable stereophotogrammetric systems are being proposed, as they are more practical and easier to use. Objective The aim of this work was to analyze the accuracy and reproducibility of a portable 3D stereophotogrammetric system (Vectra H1, Canfield, Fairfield, NJ, USA) in measuring soft facial tissues of 30 participants, defining measures of a cube and comparing these measurements with those obtained by a set 3D stereophotogrammetric system (Vectra M3, Canfield, Fairfield, NJ, USA) with previously validated accuracy and reproducibility through quantitative analysis of possible errors. Material and method Thirty temporary landmarks were used to measure (in mm) 34 distances in 30 participants (n = 30). Regarding the cube, 12 angles and 9 linear distances were evaluated. Result The results obtained by the established methodology indicated that the Vectra H1 portable system has shown accuracy and reproducibility equal to that of the Vectra M3 set system. Conclusion Data analysis and correlation to literature findings show Vectra H1's capability to reliably capture tridimensional images, which makes it practical for use in diverse clinical applications.